GLIPR1L1 is an IZUMO-binding protein required for optimal fertilization in the mouse - Avinash S. Gaikwad; Amanda L. Anderson; D. Jo Merriner; Anne E. O’Connor; Brendan J. Houston; R. John Aitken; Moira K. O’Bryan; Brett Nixon (BMC Biology, 2019)
Abstract Background The sperm protein IZUMO1 (Izumo sperm-egg fusion 1) and its recently identified binding partner on the oolemma, IZUMO1R, are among the first ligand-receptor pairs shown to be essential for gamete recognition and adhesion. However, the IZUMO1-IZUMO1R interaction does not appear to be directly responsible for promoting the fusion of the gamete membranes, suggesting that this critical phase of the fertilization cascade requires the concerted action of alternative fusogenic machinery. It has therefore been proposed that IZUMO1 may play a secondary role in the organization and/or stabilization of higher-order heteromeric complexes in spermatozoa that are required for membrane fusion. Results Here, we show that fertilization-competent (acrosome reacted) mouse spermatozoa harbor several high molecular weight protein complexes, a subset of which are readily able to adhere to solubilized oolemmal proteins. At least two of these complexes contain IZUMO1 in partnership with GLI pathogenesis-related 1 like 1 (GLIPR1L1). This interaction is associated with lipid rafts and is dynamically remodeled upon the induction of acrosomal exocytosis in preparation for sperm adhesion to the oolemma. Accordingly, the selective ablation of GLIPR1L1 leads to compromised sperm function characterized by a reduced ability to undergo the acrosome reaction and a failure of IZUMO1 redistribution. Conclusions Collectively, this study characterizes multimeric protein complexes on the sperm surface and identifies GLIPRL1L1 as a physiologically relevant regulator of IZUMO1 function and the fertilization process.